(untitled) (Al-Mansour Journal, 2022)
The modern communication systems consider the secure information transmission as an important condition to judge the successful of them. Therefore, the nowadays research focused on the development the cipher algorithms to overcome the cleared drawbacks. Rivest cipher (RC4) algorithm, adopted by wired equivalent piracy (WEP) in IEEE802.11 standard as a cryptographic algorithm, is one of the ciphering methods that suffers from numerous weaknesses. These weaknesses include in the algorithm design itself as well as the problem of attaching the WEP by hackers. As a result, these weaknesses encourage the hackers to attach the transmission information. In this paper, a modified cipher algorithm is presented, which combines the RC4 and developed version of Hill cipher algorithms. The objective of the proposed algorithm is to encrypt the plain textin two levels. Firstly, this text is encrypted utilizing the well-known RC4 and secondly the resulting ciphered text is encrypted using the modified Hill algorithm. The output text is the results of the introduced algorithm of this paper with high security and resiliency against the attaching actions. The proposed algorithm is simulated using C++ environment and the achieved results have been compared to the classic RC4. A superior performance has been recorded for the proposed algorithm in comparison with RC4.